An Introduction to Methanol as a C1 Building Block - Ansari T.; Indra A. (My University, 2025)
The worldwide industrial and academic domain requires green, cost-effective, nontoxic, and easily available C1 building block(s) for the synthesis of organic compounds and their transformation into value-added chemicals. In this context, methanol (MeOH) was found to be a suitable building block to form C–N, C–O, and C–C bonds, essential for the synthesis of diverse organic compounds. The traditional methods for the introduction of methyl (Me) group in the organics suffer from the use of hazardous and toxic reagents like MeI, diazomethane, Me-triflate, trimethyloxonium tetrafluoroborate, and dimethyl sulfate. As a result, most of the recent studies on organic methylation (Me-ation) reactions rely on MeOH as the C1 building block while Ru or Ir-based compounds have been used as the catalysts. Looking at the sustainability and cost-effectiveness, further, 3d-transition metal (TM)-based catalysts have been widely explored for the thermocatalytic, electrocatalytic, and photochemical reactions using MeOH as the C1 source. Apart from this, the two most significant characteristics of MeOH from a human perspective are its severe toxicity and its superiority as a solvent. In this chapter, we have described the recent progress in the field of organic transformation using MeOH as the C1 building block and further, the challenges and prospects of the field have been described. © 2024 Elsevier Inc. All rights are reserved, including those for text and data mining, AI training, and similar technologies.